When Does FDI Have Positive Spillovers? Evidence from 17 Transition Market Economies - Yuriy Gorodnichenko; Jan Svejnar; Katherine Terrell (Institute for the Study of Labor (IZA), 2013)
We use rich firm-level data and national input-output tables from 17 countries over the 2002-2005 period to test new and existing hypotheses about the impact of foreign direct investment (FDI) on the efficiency of domestic firms in the host country (i.e., spillovers). We document that backward linkages have a consistently positive effect on productivity of domestic firms while horizontal and forward linkages show no consistent effect. We also examine how the strength of spillovers varies by sector, FDI source, business environment (corruption, red tape, level of development), firm's distance to the technological frontier, education of workers, and other firm- and country-specific characteristics.
Keywords: F23; M16; O16; P23; 330; FDI; spillovers; transition economies; efficiency